Marketing Strategy to Increase the Portfolio of Berkah Pension Financing Products at PT. Bank Syariah Indonesia Medan City - Zahra, Fairuz Azzahra Irsyad; Marliyah; Atika (LP2M IAIN Palopo, 2025)
Bank Syariah Indonesia's Berkah Pension Financing product has significant potential, but its portfolio remains suboptimal despite intensive marketing strategies. This study aims to assess the effectiveness of marketing strategies in enhancing this product portfolio. A qualitative method was used, with a systematic literature review of articles from Scopus and Google Scholar. The results indicate that the marketing mix, sharia approach, and digitalization have a positive impact on customer interest, but are still hampered by low technology literacy and adoption among retirees. A more integrated and educational strategy is needed to support sustainable product growth. Keywords: Marketing Strategy, Sharia Financing, Sharia Bank